Reap the wild wind [offshore wind farm]. - Mandelbaum, R. (IEEE spectrum)
The worlds largest offshore wind farm is being built at Horns Rev (Reef) in the often turbulent seas off Denmark. The 80 towers in 20 km2 of sea will be capable of generating 160 MW of power. Elsam expects Horns Rev to make 600 GWh of electricity a year, 2% of the country's consumption. This paper discusses the construction of the wind farm.